2022
DOI: 10.37934/araset.28.2.199210
|View full text |Cite
|
Sign up to set email alerts
|

A Multistage Methodology Approach for Constraints Prioritisation of Facility Layout Problem (FLP) in Enhancing the Performance of Building Energy Efficiency

Abstract: Facility Layout Problem (FLP) is gaining increasing attention among researchers; it is a term relating to the poor layout of facilities as a significant contributing factor of poor performance. FLP is of paramount importance when determining inefficiencies in large room layouts, such as a library building, since the building’s layout closely influences air distribution and impacts on human comfort. Thus, this can lead to unnecessary high energy use to mitigate any inefficiencies. This problem is classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…This situation has shown that a comprehensive and accurate assessment of the power transformer in operation is crucial for the operation of the plant, and that a failure of this strategic unit will result in a significant loss of revenue. In general, production efficiency is very important, with power interruptions being a serious problem that can lead to losses, as reported in [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This situation has shown that a comprehensive and accurate assessment of the power transformer in operation is crucial for the operation of the plant, and that a failure of this strategic unit will result in a significant loss of revenue. In general, production efficiency is very important, with power interruptions being a serious problem that can lead to losses, as reported in [2][3][4].…”
Section: Introductionmentioning
confidence: 99%